P333Left atrial function by echocardiography is independent of degree of left atrial electrical scar. (18th June 2020) - Gallen, R; Herczeg, S; Mcgorrian, C; Carron, J; Walsh, K; Keelan, T; Galvin, J; Szeplaki, G; Keaney, J
Abstract: Introduction: Assessment of left atrial function via transthoracic echocardiography (TTE) is performed most commonly by measuring the transmitral A wave in sinus rhythm. Left atrial (LA) fibrosis plays an important role in the pathogenesis and perpetuation of Atrial Fibrillation (AF). It may be identified by bipolar voltage (BiV) mapping, which can easily be performed at the beginning of a Pulmonary Vein Isolation (PVI) procedure. The relationship between the degree of LA fibrosis, characterised with mapping, and LA function, determined by echocardiography, has not previously been elucidated. Methods: Patients were enrolled in a project to evaluate the degree of fibrosis during PVI procedures. Pre-procedure TTEs of those presenting in sinus rhythm were assessed and the transmitral A wave was measured and compared to the degree of scarring seen. The high density electroanatomic maps (HD-EAMs) created during the PVIs were analysed using a novel VHA algorithm after the procedure. All points with voltages < 0.5mV were defined to have electrical scar. Patients were classified into 4 quartiles based on the levels of scar seen (Figure 1). Results: 39 patients were included in the evaluation. Average age was 60.6 +/- 13.2 years. 32 (82.0%) of the patients were male. Mean CHADS2VASc score was 1.5. The mean percentage of scar was calculated as 19.6 +/- 15.9%. The average A wave was 0.62 +/- 0.18 ms-1. Pearson's correlation coefficient showed no relationship between LA scar and either A wave velocities (r = 0.26, p = 0.11) or E:A ratio (r=-0.02, p = 0.91). A significant correlation between A wave velocity and CHADS2VASc was observed (r = 0.49, p = 0.001). Conclusion: Our study demonstrates no relationship between degree of LA scarring and reduced LA function on TTE as assessed by the A wave. It has been established that structural remodelling in AF (such as atrial dilatation) may occur independently of the electrical remodelling. A potential explanation for our findings is that the electrical scarring in AF, which results in alterations in refractory periods, precedes the negative remodelling which ultimately results in reduced atrial function. This hypothesis would need to be further evaluated in larger studies.